Relationship between Cardiovascular Diseases and Periodontal Disease – A Systematic Review - Hashmat Gul; Abdullah Imtiaz; Sehrish Sharif; Ali Abdullah; Saba Rehman; Atiqa Bashir (Life and Science)
To review and explore the published literature to establish an association between cardiovascular diseases and periodontal ailments, identifying shared risk factors, examining potential mechanisms, and assessing the clinical impact of this association. The systematic review was conducted at Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan from April 2023 to September 2023. A literature search was carried out following PRISMA guidelines using suitable databases, such as ScienceDirect and PubMed, by entering keywords, e.g., 'Periodontal disease and CVDs', 'Periodontal disease and heart disease', 'Periodontitis and CVDs', and 'Periodontitis and heart disease', to find relevant articles published between 2014 and 2023, as per the set inclusion and exclusion criteria. Shortlisted articles were assessed by four reviewers, followed by closer scrutiny by an additional two reviewers to ensure their suitability for final inclusion. Finally, a Qualitative assessment of included studies was done to minimize the risk of bias. Of the 97 studies found, only 10 (10.31%) met the inclusion criteria. The common tests run to identify periodontal diseases were periodontal pocket depth, complete visual oral examination, including radiograph examinations, and plaque index monitoring. To assess patients' cardiovascular health, polymerase chain reactions (PCRs), blood picture, Platelet function tests, blood pressure measurement, and testing for biomarkers were conducted. Out of the 10 included articles, 3 showed low bias, 4 articles showed medium bias, and 3 showed high bias. This systematic review revealed a positive correlation between, cardiovascular diseases, and periodontal health. Collaboration between dental and cardiovascular experts, coupled with advanced research methods, is essential for a profound understanding of these connections, thus enabling tailored interventions, offering significant improvements in both cardiovascular and periodontal health.